The Effect Of Dynamic Stretching On Musculoskeletal Disorders (MSDs) In Smoked Fish Workers - Nur Cahyani Amaliawati Rahmat; Yuliani Setyaningsih; Suroto Suroto (Jurnal Keterapian Fisik, 2021)
Background: Fish can be processed and preserved in a variety of ways, including smoking. The workers' activities are repetitive, requiring them to sit in an unergonomic position for extended periods of time. Unnatural work attitudes and monotonous work might result in workers complaining of MSDs. The purpose of this study is to analyze the effect of giving dynamic stretching using a hoop on MSDs complaints to fish smoking workers. Methods: This study employs a Quasy-Experimental design with a non-equivalent control group. The sample for this study comprised 25 respondents in the treatment group and 25 respondents in the control group who met the inclusion criteria by purposive sampling are 35-60 years old, willing to be a respondent and communicative, and attend the pre-post test. The NRS was employed as the research instrument, starting from a scale of 0 to 10. A scale of 0 means no pain, 1-3 means mild pain, 4-6 means moderate pain, 7-10 means severe pain. Analyses of data using the Mann-Whitney statistical test. Results: The result of this study is that there is a significant difference in the MSDs complaint scale based on the Mann Whitney test between the treatment group and the control group with a p-value of 0.000 (p<0.05). Conclution: Dynamic stretching using a hoop has an effect on reducing MSDs complaints in fish smoking workers.